2019
DOI: 10.1155/2019/4536302
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Low-Density Lipoprotein Receptor-Related Proteins 5, 6, and 8 in Cancer: A Review

Abstract: Low-density lipoprotein receptor (LDLR) has been an object of research since the 1970s because of its role in various cell functions. The LDLR family members include LRP5, LRP6, and LRP8. Even though LRP5, 6, and 8 are in the same family, intriguingly, these three proteins have various roles in physiological events, as well as in regulating different mechanisms in various kinds of cancers. LRP5, LRP6, and LRP8 have been shown to play important roles in a broad panel of cancers. LRP5 is highly expressed in many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 34 publications
0
38
0
Order By: Relevance
“…The low-density lipoprotein receptor‐related protein families are transmembrane proteins, limited to the regulation of cholesterol homeostasis by receptor‐mediated endocytosis of lipoprotein particles; however, there is growing experimental evidence that the other members of the gene family have additional physiological functions, including signal transduction 4. Members of the LRP family, including LDLR related protein 1 (LRP1), LRP2/glycoprotein330/megalin, very low-density lipoprotein (VLDL) receptor (VLDLR); LR11 (also known as sorLA); apolipoprotein E (apoE) receptor type 2 (apoER2, LRP8, LR7/8B); LRP3, MEGF7/LRP4, LRP5, and LRP6, LR32 (also called LRP1B), as well as the LRP11 5,6. Many studies have reported that family members LRP1 and LRP1B serve as prognostic markers in colon cancer, breast cancer, thyroid cancer, urothelial and clear-cell renal cell carcinoma that they play important roles in carcinogenesis 715.…”
Section: Introductionmentioning
confidence: 99%
“…The low-density lipoprotein receptor‐related protein families are transmembrane proteins, limited to the regulation of cholesterol homeostasis by receptor‐mediated endocytosis of lipoprotein particles; however, there is growing experimental evidence that the other members of the gene family have additional physiological functions, including signal transduction 4. Members of the LRP family, including LDLR related protein 1 (LRP1), LRP2/glycoprotein330/megalin, very low-density lipoprotein (VLDL) receptor (VLDLR); LR11 (also known as sorLA); apolipoprotein E (apoE) receptor type 2 (apoER2, LRP8, LR7/8B); LRP3, MEGF7/LRP4, LRP5, and LRP6, LR32 (also called LRP1B), as well as the LRP11 5,6. Many studies have reported that family members LRP1 and LRP1B serve as prognostic markers in colon cancer, breast cancer, thyroid cancer, urothelial and clear-cell renal cell carcinoma that they play important roles in carcinogenesis 715.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, some LRPs have been identified as direct molecular targets for BC. LRP6 is probably the most promising target in the TNBC with its overexpression leading to Wnt signaling pathway activation together with tumorigenesis promotion ( 5 ). Several drugs such as salinomycin, prodigiosin, and niclosamide indeed induce LRP6 phosphorylation and degradation leading to decreased tumor growth ( 49 , 50 , 95 ).…”
Section: A Better Understanding Of Lrp Functionalities May Lead To Efmentioning
confidence: 99%
“…Lrp8 is located on chromosome 3 and has a length of 3291 bp, and it encodes a protein called low-density lipoprotein receptor-related protein 8. In recent years, Lrp8 has been revealed to play a role in cell development and migration via the regulation of the canonical Wnt/β-catenin signaling pathway [33]. Hence, Lrp8 is actively involved in the regulation of tumor and bone diseases [31,32].…”
Section: Hub Genesmentioning
confidence: 99%